Dynamics of HIV-1 infected population acquired via different sexual contacts route: a case study of Turkey - Hincal, E.; Sayan, M.; Baba, I.A.; Sanlidag, T.; Saad, F.T.; Kaymakamzade, B. (Bulletin of the Karaganda University. Mathematics Series, 2018)
This paper aims to study the transmission dynamics of HIV/AIDS in heterosexual, men having sex with men (MSM)/bisexuals and others in Turkey. Four equilibrium points were obtained which include disease free and endemic equilibrium points. The global stability analysis of the equilibria was carried out using the Lyapunov function which happens to depend on the basic reproduction number R0. If R0< 1 the disease free equilibrium point is globally asymptotically stable and the disease dies out, and if R0 > 1, the endemic equilibrium point is stable and epidemics will occur. We use raw data obtained from Kocaeli University, PCR Unit, Turkey to analyze and predict the trend of HIV/AIDS among heterosexuals, MSM/bisexual, and others. The basic reproduction number for heterosexuals, MSM/bisexuals, and others was found to be 1.08, 0.6719, and 0.050, respectively. This shows that the threat posed by HIV/AIDS among heterosexuals is greater than followed by MSM/bisexuals, and than the others. So, the relevant authorities should put priorities in containing the disease in order of their threat.